2021
DOI: 10.37185/lns.1.1.172
|View full text |Cite
|
Sign up to set email alerts
|

Empathy among Medical Students Studying Different Curricula: A Comparative Study

Abstract: Objective: To determine and compare empathy among medical students, studying two different curricula.Study Design: Cross Sectional.Place and Duration of Study: The study was carried out at the Department of Community Medicine of WahMedical College, Wah Cantt from January 2018 to June 2018.Materials and Methods: The study was carried out on second and fourth year MBBS students. The sample sizewas 90, calculated by Open Epi calculator and the students were selected by using stratified random samplingtechnique. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Using the TEQ and other tools, Bhatia G et al in India and Imran SS et al in Pakistan also concluded that empathy scores according to TEQ decline as the year progresses [17,23]. The low degree of empathy among medical students and its decline as their medical education advances has been a source of worry in several research.…”
Section: Discussionmentioning
confidence: 99%
“…Using the TEQ and other tools, Bhatia G et al in India and Imran SS et al in Pakistan also concluded that empathy scores according to TEQ decline as the year progresses [17,23]. The low degree of empathy among medical students and its decline as their medical education advances has been a source of worry in several research.…”
Section: Discussionmentioning
confidence: 99%